Robustness of kinematic weighting and scaling concepts for musculoskeletal simulation. Issue 7 (19th May 2017) - Schellenberg, Florian; Taylor, William R.; Jonkers, Ilse; Lorenzetti, Silvio
Abstract: Musculoskeletal modelling is widely used to estimate internal loading conditions. In order to optimise robustness and reduce errors between the subject-specific reference motion data (RMD) and the musculoskeletal simulation, 90 permutations of kinetic and kinematic data were analysed during split squats. A ranking for the scaling and kinematic weighting concepts based on the RMS errors when including functional centres of rotation ( fCoRs ), joint angles, and skin markers, revealed that analyses should include fCoR in the scaling and the simulation processes, as well as an automated weighting procedure including all attached skin markers for optimal registration of the musculoskeletal model to the RMD.